Analysis of Gempol Muslim Society’s Interest on The Use of E-Toll Card - Azizah, Zumrotul; Demila, Demila (Majapahit Journal of Islamic Finance and Management, 2021)
This research is motivated by problems often occuring on toll roads, especially during transactions at the gate. Transactions that occur between officers and drivers take a long time because toll officials have to check the origin of the vehicle to determine the rate, then calculate the change. To anticipate congestion on toll roads, especially during peak days and hours because the queues at the toll booths are too long, a higher speed is required in making toll payments using the electronic toll service (e-Toll) at the Automatic Toll Gate (GTO). This research is a qualitative research, the data is obtained by natural setting. Data collection techniques were carried out by observation, interviews and documentation. The outline in collecting the data is that the author will find out about whether the Muslim community of Gempol knows about the e-Toll card, the community uses e-Toll for what reasons, then the researcher will find out the extent of interest in using e-Toll cards in the region of Gempol. The results showed that; first, the interest of the Gempol Muslim community in using e-Toll cards is still low because it is far from the target number. According to predictions of Jasa Marga employees, it still reached 17 percent as of January 2018, while the target figure is 100 percent. In addition, there are also many pros and cons of the bank's new product in the form of e-Toll. E-Toll card has no significant relationship with reducing congestion, although as of October almost 100% of toll gates in Indonesia use GTO, but for congestion it could be due to vehicle volume, road engineering, accidents, narrowing of lanes, reduction of lanes, number of gates tolls, and the number of toll gates opened. Second, the factors influencing the Muslim community of Gempol on the use of e-Toll cards are government regulations, the influence of advertisements and the public feel the benefits obtained from e-Toll.